Low-voltage Ride-through Methods for Grid-connected Photovoltaic Systems in Microgrids: A Review and Future Prospect - Haval Sardar Kamil; Dalila Mat Said; Mohd Wazir Mustafa; Mohammad Reza Miveh; Nasarudin Ahmad (Institute of Advanced Engineering and Science, 2018)
Power quality is a concern for utility and grid operators due to a large penetration of intermittent and stochastic renewable power generation sources. One of the major concerns, when designing and controlling grid-feeding photovoltaic (PV) inverters is meeting the grid requirements. International grid requirements demand low-voltage ride-through (LVRT) capability and maintaining grid functionality during fault conditions. This paper presents a comprehensive review for several control techniques to assure the LVRT capability of grid-feeding converters as well as discussing their respective advantages and limitations in detail. Areas for further research are identified afterwards. Finally, the conclusion gives a brief summary and critique of the findings.